The Effect of Working Capital Management on Company Profitability (Case Study on Food and Beverage Companies Listed in Indonesia Stock Exchange) - Eva Yuniarti Utami; Marwan Asri (Syntax Literate, 2023)
This research examines the effect of working capital management on profitability level of food and beverage companies in Indonesia. Working capital management consists of accounts receivable period, inventory period and accounts payable period. Samples were taken by purposive sampling with certain criteria which are: the companies must have been listed on BEI in research period, as well as must have published their financial statements during year 2014-2018. The method used in this research is multiple linear regression analysis. The result of multiple linear regression test explains that working capital management variables have effect on probability of the company. This shows that the company that is accelerating the period of collection customer debt as well as delaying payment due to suppliers do necessarily get bigger profit. But accelerating the inventory conversion period does not have a significant effect on company profits.